2008
DOI: 10.1007/s10267-007-0400-6
|View full text |Cite
|
Sign up to set email alerts
|

Use of single-protoplast isolates in the study of the mating phenomena of Rhizoctonia solani (Thanatephorus cucumeris) AG-1 IC and IA

Abstract: Use of single-protoplast isolates in the study of the mating phenomena of Rhizoctonia solani (Thanatephorus cucumeris) AG-1 IC and IA Abstract This study evaluates the effectiveness of using single-protoplast isolates (SPIs) to study the mating phenomena of Rhizoctonia solani AG-1 IC and IA. SPIs obtained from three fi eld isolates (F-1, Rh28, and RO2) of AG-1 IC were paired with representative single-basidiospore isolate (SBI)-M1/-M2 testers, each from their own fi eld isolates, or paired in all possible comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Consequently, most investigations have focused on haploid protoplasts rather than single basidiospores. Such studies have confirmed that AG 1‐IA can form both homokaryotic and heterokaryotic progeny 12 . In addition, changes to the protoplast‐releasing procedure have been found to result in protoplasts that contain different numbers of nuclei, making them genetically different from their parental isolates 6 …”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Consequently, most investigations have focused on haploid protoplasts rather than single basidiospores. Such studies have confirmed that AG 1‐IA can form both homokaryotic and heterokaryotic progeny 12 . In addition, changes to the protoplast‐releasing procedure have been found to result in protoplasts that contain different numbers of nuclei, making them genetically different from their parental isolates 6 …”
Section: Introductionmentioning
confidence: 82%
“…Ten mycelial plugs (5 mm in diameter) were then cut from the intersection of the two colonies and used to inoculate Potato Dextrose Broth (PDB). After 24 h of dark incubation at 25°C with shaking (120 rpm), the mycelium was removed with forceps, washed in an osmotic medium (0.98 m MgSO 4 , 8.4 m m Na 2 HPO 4 , 1.6 m m NaH 2 PO 4 ), 44 and ground with a sterile pestle and mortar before being transferred to a 250‐ml flask containing 100 ml CM medium (5 g L −1 glucose, 5 g L −1 malt extract, 5 g L −1 yeast extract), 12 and dark‐incubated at 25°C with shaking (120 rpm) for 24 h. The mycelium was then collected by centrifugation at 290 g for 10 min. After the supernatant had been removed, the mycelium was washed in 10 ml osmotic medium and centrifuged as before.…”
Section: Methodsmentioning
confidence: 99%
“…When one of the homokaryons was paired separately with the other three homokaryons, none of the parings showed tuft formation, indicating that all of them belonged to the same type of homokaryon. Since R. solani AG1-IC has been reported to produce two types of homokaryons (Ou et al [ 2008 ]), this type of homokaryon was designated as A, while the other not yet found homokaryon type was designated as B. The heterokaryon was designated as AB.…”
Section: Methodsmentioning
confidence: 99%
“…In R. solani , homokaryotic isolates are normally derived from single basidiospores (Whitney and Parmeter [ 1963 ]) or protoplasts (Phillips [ 1993 ]). Since R. solani AG1-IC is heterothallic (Qu et al [ 2008 ]) and our numerous attempts to induce basidiospore formation of isolate CH-1 also were not successful, protoplasts were used for preparation of homokaryons. In the process of homokaryon preparation, it was found that colonies derived from protoplasts of isolate CH-1 consisted of heterokaryon and one type of homokaryon only.…”
Section: Introductionmentioning
confidence: 99%
“…Regeneration of protoplasts of R. solani was usually carried out on agar media [15,16,19,26]. When tested in liquid media, Robin-…”
Section: Figurementioning
confidence: 99%